METAPHYSICAL POSTULATES OF EDUCATIONAL PRAXES: APPEAL TO THE FIRST PRINCIPLES OF METAPHYSICS AND THE PRINCIPLES OF BEING. - KAUKA, ELVIS OMONDI (IJRDO- Journal of Educational Research, 2017)
This study sought to investigate the metaphysical premises upon which educational praxes situate themselves. The study contends that education is a metaphysically laden activity. It uses analytic and speculative methods to pinpoint areas of metaphysical concern with special interest on the learner and the learning process. The study proceeds by elucidating metaphysics in relation to education, then analyses the first principles of metaphysics and how each one of them inform education praxis. In the second section the principles of being are discussed and applied on education. These principles include Potency and act, essence and existence, and causality and participation. The conclusion drawn in this study, points to the fact that education revolves around a composite being(with form and matter) and so cannot be handled simplistically , an Essential being and so its universal value should not be eroded during education and existential being with individuated experiences; pedagogical or otherwise.